RECONCILING CONTROL, ACCOUNTABILITY, AND SUSTAINABILITY: A CONCEPTUAL SYNTHESIS OF MEDICAL WASTE GOVERNANCE, PERFORMANCE MEASUREMENT SYSTEMS, AND THE LEVERS OF CONTROL IN PUBLIC HOSPITALS - Prayudi, Made Aristia; Armini, Luh Nik; Mursito, Kendhy (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Medical waste management has become an increasingly urgent governance concern for public hospitals, particularly in developing and emerging economies where institutional complexity, fiscal constraints, and regulatory ambiguity persist. Although improper waste handling poses severe public health risks, the persistent failures observed across hospitals cannot be explained through technical or operational lenses alone. This conceptual paper synthesizes three major bodies of literature—medical waste governance, performance measurement systems (PMSs), and Simons’ Levers of Control (LoC)—to develop an integrated understanding of how organizational control architectures shape managerial attention, accountability, and environmental performance. The review shows that weak PMS design, fragmented control systems, and inconsistent enactment of control levers collectively contribute to the gap between formal regulatory expectations and actual waste-handling practices. It also highlights empirical anomalies and theoretical tensions within LoC research, particularly its assumptions regarding lever interactions and synergy when applied to resource-constrained, bureaucratic health systems. The Indonesian public-hospital setting illustrates how autonomy and dependence coexist, complicating efforts to institutionalize effective waste governance. By consolidating dispersed insights from multiple disciplines, this paper advances a more comprehensive and context-sensitive explanation of medical waste governance and offers a foundation for future empirical research on the interplay between PMSs, control levers, and environmental stewardship in public healthcare.